Longman dictionary of contemporary English (Harlow, Essex Pearson Education Limited, 2014)
The sixth edition of this best-selling dictionary ensures students produce more accurate English both in writing and speaking with 230,000 words, phrases and meanings. Now with expanded Grammar information, students get extra help with grammar patterns and using the correct tenses. The integrated Collocations Dictionary shows learners which words to use together, while the integrated Thesaurus helps them to expand their vocabulary. Register Notes focus on the differences between spoken and written English. The brand new online resources offer the entire content of the dictionary plus additional innovative functionality to facilitate customisable teaching and learning, and a wealth of practice so that users focus on the words that they want to learn
The Longman Dictionary of Contemporary English, is a comprehensive dictionary ever with 230,000 words, phrases and meanings
"For advanced learners"
2 21
Keywords: English language -- Dictionaries